2019
DOI: 10.1097/pq9.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Timely Access to Mental Health Services for Patients with Pain

Abstract: Introduction: Efficient access to pediatric mental health services is a growing concern as the number of patients increases and outpaces efforts to expand services. This study outlines interventions implemented using quality improvement (QI) science and methodology to demonstrate how a clinic embedded in a large children’s hospital can improve access to the first appointment for a population seeking pain management services. Methods: A process improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Process efficiency or pathway interventions used a variety of strategies to improve patient flow, such as elements of lean thinking approaches, changes to referral criteria, new patient pathways and changes to the model of care such as increased use of groups. There were 11 studies in this category (Table 2 ), including three in autism services (Austin et al, 2016 ; Lemay et al, 2018 ; Rutherford et al, 2018 ), two in occupational therapy services (Horton & Hall, 2008 ; F. Millar et al, 2013 ), four in mental health (Butz et al, 2019 ; Rocks et al, 2020 ; Wenning & King, 1995 ; Woodhouse, 2006 ) and one each in early intervention(Bell et al, 2010 ) and general rehabilitation (Camden et al, 2013 ). All but one (Rocks et al, 2020 ) reported reductions in waiting time (Figure 2b ), with eight of these cases being reductions of more than 50%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Process efficiency or pathway interventions used a variety of strategies to improve patient flow, such as elements of lean thinking approaches, changes to referral criteria, new patient pathways and changes to the model of care such as increased use of groups. There were 11 studies in this category (Table 2 ), including three in autism services (Austin et al, 2016 ; Lemay et al, 2018 ; Rutherford et al, 2018 ), two in occupational therapy services (Horton & Hall, 2008 ; F. Millar et al, 2013 ), four in mental health (Butz et al, 2019 ; Rocks et al, 2020 ; Wenning & King, 1995 ; Woodhouse, 2006 ) and one each in early intervention(Bell et al, 2010 ) and general rehabilitation (Camden et al, 2013 ). All but one (Rocks et al, 2020 ) reported reductions in waiting time (Figure 2b ), with eight of these cases being reductions of more than 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Rates of missed appointments were reported in two studies using rapid response interventions (Clemente et al, 2006 ; Evans, 2014 ) and two studies using process redesign interventions (Butz et al, 2019 ; Woodhouse, 2006 ). Both reported reductions in the proportion of people who missed appointments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, access to mental health care is difficult for many of our youth (Butryn et al, 2017). There is a shortage of community mental health providers, and the wait time for an appointment is an average of 106 days (Cama et al, 2017; Butz et al, 2019). There are further disparities in access to mental health care among youth of color, youth with severe emotional and behavioral disabilities, and among families living in poverty (American Psychological Association, 2017; Alegria et al, 2015; Inkelas et al, 2007; Stiffman et al, 2004).…”
mentioning
confidence: 99%